Metals in Oncology: An Overview - Yadav, Ram Nath Prasad (Academic Voices: A Multidisciplinary Journal, 2013)
This paper is an attempt to survey the literature of metal in oncology and also to give relative insight of effectiveness of different metals and their compounds against tumors cell lines. In this article I have summarized the anticancer activities of the certain active metals such as arsenic, tin, gallium, bismuth, and antimony. Arsenic is present in the anomaly of displaying anti-cancer and oncogenic properties simultaneously. Organic compounds of tin exhibit anti-cancer activity similar to cis-platin compound of platinum. The anti-proliferative effect of gallium could be related to its completion with iron atom. Bismuth directly affects Helicobacter pylori and gastric lymphoma: the effect of bismuth complexes of 6-mercaptopyrine are promising. Some antimony organic compounds show interesting result. Academic Voices, Vol. 2, No. 1, 2012, Pages 54-58 DOI: http://dx.doi.org/10.3126/av.v2i1.8288